1985
DOI: 10.1017/s0014479700012229
|View full text |Cite
|
Sign up to set email alerts
|

Weather Factors Affecting the Response of Maize to Planting Dates in a Tropical Rainforest Location

Abstract: S U M M A R YSimple linear correlations, stepwise multiple regressions and path-coefficient analyses were used to determine the relation between grain yield of maize (Zea mays L.) and weather factors in a three year study involving several planting dates within each year. Maximum and minimum relative humidity, which demonstrated negative relationships with yield, were the most reliable factors, both directly and indirectly, for predicting yield. Temperature (including accumulated heat units), sunshine hours an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…E. oleifera is characterised by a procumbent trunk and slow stem growth, with a mature height of 1 .5 to 2 .7 m, while E. guineensis is characterised by rapid height increment and the trunk reaches a height of 15 to 18 m . E. oleifera is generally lower yielding than E. guineensis and results summarized by Mennier & Hardon (1976) showed NB to be comparable in both species but MBW is (Fakorede, 1979 ;Fakorede & Opeke, 1985 analyses were done . It seems therefore that palms having the potential to produce more fruits (i .e .…”
Section: Resultsmentioning
confidence: 97%
“…E. oleifera is characterised by a procumbent trunk and slow stem growth, with a mature height of 1 .5 to 2 .7 m, while E. guineensis is characterised by rapid height increment and the trunk reaches a height of 15 to 18 m . E. oleifera is generally lower yielding than E. guineensis and results summarized by Mennier & Hardon (1976) showed NB to be comparable in both species but MBW is (Fakorede, 1979 ;Fakorede & Opeke, 1985 analyses were done . It seems therefore that palms having the potential to produce more fruits (i .e .…”
Section: Resultsmentioning
confidence: 97%
“…Therefore, when more than two variables are involved, the correlations per se do not give the complete picture of their relationships. The path coefficient analysis is particularly useful for the study of the cause and the effect relationship, because it simultaneously considers several variables in data set to obtain the coefficients (Fakorede and Opeke 1985). The direct and indirect effects of agronomic traits on CF, RC and PPE are shown in Table 3.…”
Section: Path Coefficient Analysismentioning
confidence: 99%
“…Aliyu et al (2000) reported that where there is a characterization of association between characters, correlation analysis helps to determine the type and magnitude of the association between a pair of characters. It has even been reported that where there are more than two variables, using correlation coefficient alone does not give good picture of the interrelationship (Fakorede and Opeke, 1985). Therefore, path coefficient analysis is used where more than two characters are to be considered.…”
Section: Introductionmentioning
confidence: 99%